Optimalisasi Sistem Pembelajaran Private Sebagai Upaya Peningkatan Pemahaman Nilai-Nilai Ajaran Islam di Desa Peria-ria - Mhd Fiqri Aditya; Ellisa Fitri Tanjung (Sekolah Tinggi Ilmu Administrasi Yappi Makassar, 2025)
This research aims to evaluate how the optimization of the private learning system contributes to improving the understanding of Islamic values among students and the community in Peria-ria Village, Biru-Biru District, Deli Serdang Regency. Using a qualitative descriptive approach, this study explores how private learning methods are implemented in Islamic Religious Education (PAI) and how they impact learners’ comprehension, character development, and social awareness. Data were collected through direct observation, in-depth interviews with teachers, community leaders, and students, as well as documentation during the 2025 Independent Community Service (KKN Mandiri) program conducted by Universitas Muhammadiyah Sumatera Utara. The findings show that private learning based on Islamic values effectively enhances students’ understanding of akidah, ibadah, and akhlaq in a more interactive and contextual way. The learning process encourages not only religious knowledge but also positive behavioral change, responsibility, and social solidarity within the community. Although this model requires consistent mentoring, it provides valuable insights for developing more adaptive and sustainable Islamic education strategies at the community level.